سقوط الحضانة عن الأم الحاضنة بين الشريعة الإسلامية والقانون الجزائري - دراسة مقارنة - محمد, مراد; السعيد, صالحي; إدريس, عبيد (University of eloued جامعة الوادي, 2022)
"ملخص موضوع المذكرة تحت عنوان: ""سقوط الحضانة عن الأم الحاضنة بين الشريعة الإسلامية والقانون الجزائري-دراسة مقارنة-""والإشكالية الرئيسية لهذه المذكرة تدور حول معالجة المشرع الجزائري لمسقطات الحضانة عن الأم إزاء ما أقرته أحكام الفقه الإسلامي. وقد اشتمل الموضوع على فصلين: الأول وضح ماهية الحضانة وشروط استحقاقها، والفصل الثاني عالج مسقطات الحضانة عن الأم. ومن أهم النتائج التي توصلنا إليها في بحثنا هذا، موافقة المشرع الجزائري لفقهاء الشريعة الإسلامية في أسباب سقوط حضانة الأم واختلافهم في بعض التفاصيل، التي راع مصلحة المحضون فيها، وترك للقاضي السلطة التقديرية في ذلك. وأوصى الموضوع على توفير آليات في الجانب النفسي والاجتماعي والديني, لمساعدة القضاة في اجتهادهم والحث على المزيد من الدراسات حول المستجدات في الاجتهادات الفقهية، بالنسبة لحالات سقوط الحضانة ، لما له من تأثير على مصلحة الأم الحاضنة. الكلمات المفتاحية: الحضانة؛ الأم؛ سقوط الحضانة؛ الفقه الإسلامي؛ القانون الجزائري. ""Abstract The aim of this dissertation, titled ""Maternal Loss of Child Custody in Islamic Sharia and Algerian Law: A Comparative Study,"" is to examine and discuss how Algerian legislators have dealt with the maternal loss of child custody in light of Islamic Sharia. The nature of the subject necessitates the division of the subject into two chapters: the first explains the nature of child custody and its requirements; and the second deals with the causative factors of the maternal loss of child custody. One of the most significant findings of this research is that the Algerian legislator agreed with Islamic Sharia on the causes of the maternal loss of child custody with some disagreements about some details, taking into account the interests of the child, and leaving the judge with the right of discretion regarding that. Due to the importance of the subject of maternal custody, the research recommends the provision of psychological, social, and religious frameworks that facilitate and encourage judges’ research engagement on the latest studies and findings of Sharia scholars. Keywords: Algerian Law, Child Custody, Maternal Custody Loss, Mother, Sharia Law. "
مذكرة ماستر
Keywords: الحضانة؛ الأم؛ سقوط الحضانة؛ الفقه الإسلامي؛ القانون الجزائري.; Algerian Law, Child Custody, Maternal Custody Loss, Mother, Sharia Law.